1981
DOI: 10.1084/jem.154.3.581
|View full text |Cite
|
Sign up to set email alerts
|

Post-thymic T lymphocyte maturation during ontogenesis.

Abstract: Peripheral T lymphocytes from newborn (4-6-d-old) mice, isolated from the spleen or lymph nodes, show phenotypic features of immature cortical thymocytes, such as high frequencies of proliferating cells and of peanut lectin-binding cells. These are features of peripheral T cells of recent thymic origin, as shown by in situ labeling of thymocytes and subsequent observation of the migrants to the spleen, which were mainly peanut lectin-binding cells. The function of newborn peripheral T cells was compared, on a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
0

Year Published

1983
1983
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(22 citation statements)
references
References 28 publications
1
21
0
Order By: Relevance
“…Therefore, we can conclude that rat peripheral DP lymphocytes are partially immunocompetent T cells that belong to the CD4 cell lineage and undergo post-thymic phenotypic and functional maturation in the peripheral lymphoid tissues. Similar post-thymic differentiation processes affecting CD4 ϩ T cells have been previously reported in mice and rats (44,54,55) and have been shown to be independent of the presence of the thymus (44,56), a fact also confirmed by our results. The nature of the signal(s) required for post-thymic development of some CD4 ϩ T cells is unknown at present.…”
Section: Discussionsupporting
confidence: 81%
“…Therefore, we can conclude that rat peripheral DP lymphocytes are partially immunocompetent T cells that belong to the CD4 cell lineage and undergo post-thymic phenotypic and functional maturation in the peripheral lymphoid tissues. Similar post-thymic differentiation processes affecting CD4 ϩ T cells have been previously reported in mice and rats (44,54,55) and have been shown to be independent of the presence of the thymus (44,56), a fact also confirmed by our results. The nature of the signal(s) required for post-thymic development of some CD4 ϩ T cells is unknown at present.…”
Section: Discussionsupporting
confidence: 81%
“…The neonatal immune functionality of mammals is very limited, and during early life, it gradually starts to acquire the immune status of adults [32,33]. The impact of nutritional fatty acids on the development of the early immune system has been demonstrated to involve regulation of metabolic processes and gene expression of important proteins such as enzymes and cytokines [34].…”
Section: Discussionmentioning
confidence: 99%
“…Peripheral T cells, in absence of a thymus (4,25) or when transferred to T cell-deficient hosts (5,7,26), are capable of considerable expansion. The sequential transfer of a T cell population into successive hosts has shown that one T cell can generate up to 10 15 cells (7).…”
Section: Discussionmentioning
confidence: 99%